Teaching English Vocabulary Using Total Physical Response (Tpr) For The Third Grade Students Of Sdn Tenggak 2 Sragen In 2014/2015 Academic Year - Lirin Rintihaningrum, Anjanfiani, Aryati Prasetyarini, S.Pd., M.Pd, Siti Fatimah, S.Pd, M.Hum (2015)
In general this study aims (1) to describe the implementation of teaching English vocabulary using Total Physical Response (TPR) for the third grade students of SDN Tenggak 2 Sragen and especially (a) the objective, (b) the materials and (c) teaching procedures, (2) to describe the students response, (3) to describe the advantages and disadvantages of using Total Physical Response (TPR). The type of this research is descriptive qualitative research. The writer collects the data by observing the teaching learning process, conducting interview with teacher and students, and takes documentation during teaching-learning process. The technique for analyzing data is data reduction, data display, and conclusion. The result of this research shows that: 1) the implementation teaching English vocabulary using Total Physical Response (TPR) at the third grade of SDN Tenggak 2 Sragen, consists of the objective of teaching English vocabulary is to improve the students vocabulary mastery. The textbook used is entitled "LKS Bahasa Inggris Logika" and the material is parts of our body. There are three activities in teaching learning process, such as: opening, learning activities, and closing (2) Most of the students gave good responses. Most of them enjoyed the teaching-learning process. They were very interested in the process of learning in every meeting. (3) Using Total Physical Response (TPR), the students can easily memorize the meaning of word, because they can see the real object. However, it can be a challenge for shy students. They not brave to demonstrate the commands with the materials.